The Achievement of the Independent Curriculum on Biology Subject in Senior High School - Hartono, Adi; Mukra, Rizal; Hariyadi, Itra; Barik, Ahsanul; Syah, Putri Aulia; Camara, Jun S. (Universitas Sultan Ageng Tirtayasa, 2024)
This study aimed to analyze the achievement of the Independent Curriculum implemented in Biology subject. The research method used is a survey conducted at one of the senior high schools at Lahewa, North Nias, Indonesia. The Independent Curriculum is the latest curriculum targeted by the Ministry of Education and Culture of the Republic of Indonesia to be implemented at every level of education. This curriculum optimizes intracurricular learning content. This is intended so that students can explore concepts and strengthen competencies according to the learning needs and interests of students. Biology lessons in high school as one of the intracurricular lessons are implemented based on the Independent Curriculum. The research instrument used is a measurement of the implementation of Biology learning designed based on the indicators of the Independent Curriculum. The data analysis technique was carried out qualitatively. The results showed that the Independent Curriculum in Biology lessons has been well implemented in high schools with the expectation that Biology teachers must be able to coordinate the learning process optimally. Thus, achieving the Independent Curriculum in Biology lessons must be supported by teacher competence to optimally direct students in the learning process.